Bargaining with Non-Monolithic Players - Jean Christophe Pereau; Alejandro Caparrós; Tarik Tazdaït (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper analyses strategic bargaining in negotiations between non-monolithic players, i.e. agents starting negotiations can split up in smaller entities during the bargaining process. We show that the possibility of scission in the informed coalition implies that it loses its information advantages. We also show that when the possibility of a scission exists the uninformed player does not focus on his or her beliefs about the strength of the informed coalition but on the proportion of weak/strong players within this coalition. Finally, our results show that the possibility of a scission reduces the incentives for the leader to propose a high offer to ensure a global agreement. We apply this framework to international negotiations on global public goods and to wage negotiations.
Keywords: C72; D74; Q28; 330; Strategic bargaining; Non-monolithic players; Scission; Noncooperative game-theory; Verhandlungstheorie; Nichtkooperatives Spiel; Theorie